Factors of influence on evacuation behaviour: Survey results from the riverine floodplain communities in Bangladesh - Mondal, Md Sanaul Haque (Quaestiones Geographicae, 2021)
River floods are distinct because not all of them are destructive and typically affect the people who are living in riverine areas. Therefore, people often refuse to evacuate even when they face imminent danger. River floods are a recurrent phenomenon in Bangladesh. This research aims to analyse the flood evacuation behaviour of riverine people in Bangladesh. A total of 377 households were selected for the questionnaire survey and were interviewed from April 2019 to May 2019. Bivariate and multivariate statistics were employed to analyse riverine people’s evacuation behaviour based on their socio-demographic and economic characteristics. This study found that although 82% of the households had received flood warning messages, only 40% had evacuated. Results from multivariate analysis suggested that the age of household heads, their education, whether they are disabled/chronically ill members, their income, the height of floodwater inside the house, and the type of warning messages they receive appear to be key determinants that influenced their decisions regarding evacuation. Elderly household heads had a lower likelihood to evacuate. The results showed a negative association between early warning messages and evacuation. Household with disabled/ chronically ill member(s) was associated with a higher likelihood of evacuation. Similarly, higher water depth in the home was associated with evacuation. These findings will be helpful for policymakers to enhance awareness of riverine households.